Stories and Mathematics Come Together - Singh, Pooja Keshavan (Voices of Teachers and Teacher Educators, 2017)
An Elementary school teacher explores the use of storytelling as a pedagogic tool for teaching Algebra to her students. She discusses various sub-concepts of Algebra that are embedded into the story and the students attempt the associated worksheet. Then she discusses their textbook questions to give more practice and different contexts. Students’ response to the story and the associated tasks are heartening because of high curiosity and logical reasoning shown by them. Their agency in using all their resources to help someone in need is also very powerful. Storytelling is worth a try for teaching a subject that is usually seen as ‘difficult’ by some students.